Atomistic insight into the effects of W content on the creep behaviors of NbMoTaW high-entropy alloys - Xinyuan Zhang; Penghui Bai; Feiyang Wang; Haitao Zhao; Xiaoye Zhou; Shuize Wang; Junheng Gao; Chaolei Zhang; Hong-Hui Wu; Xinping Mao (Journal of Materials Research and Technology)
As a type of refractory high-entropy alloy (RHEA), NbMoTaW shows significant potential as a high-temperature alloy material. However, studies on its high-temperature creep behavior remain limited. In this work, we investigate Nb1-xMo25Ta25Wx (x = 10, 17, 25, 33, and 40) to examine the effect of tungsten (W) content on high-temperature creep resistance. Using molecular dynamics (MD) and Monte Carlo (MC) simulations, the deformation behavior and atomic mechanisms of NbMoTaW with varying W contents under creep loading were explored. The influence of temperature, sustained stress, and W content on creep behavior were analyzed. The results reveal that increased W content enhances the solute drag effect on other solute atoms, thus hindering grain motion and improving high-temperature creep resistance. Additionally, MC swaps increase grain-interior W content, further enhancing the high-temperature creep resistance. This study provides valuable insights into the high-temperature creep mechanisms of NbMoTaW and offers strategic guidance for designing alloy materials with superior high-temperature creep resistance.